Förderung der Sprechfertigkeit in DaF: eine qualitative Analyse zur Nutzung von ChatClass - Marques-schäfer, Gabriela; Rozenfeld, Cibele Cecilio De Faria [UNESP] (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/; Programa de Pós-Graduação em Língua e Literatura Alemã, 2021)
With the advent of mobile technologies, the development of digital tools for learning a foreign language began to grow. However, most of the tools available emphasize vocabulary learning and grammatical features, in detriment of speaking skills. This article examines ChatClass app, which was developed to fill this gap. The data was collected from a questionnaire handed out to German students of a Brazilian university. During a semester, the students used the ChatClass Deutsch app in order to improve their speaking skills. Results from the study show that the tool was considered innovative and a valid way to encourage learning and speaking, since it enables a learner-learner-oral-authentic exchange without the interference of a teacher. The article concludes that the experience has motivated the learners to express themselves more freely in the foreign language outside the classroom.
ä ö ü ß
Improving speaking skills in German as a foreign language: a qualitative research on the use of ChatClass
Keywords: speaking skills; mobile learning; chatbot; speaking strategies; speaking anxiety